Optoelectronic and thermodynamic properties, infrared and Raman spectra of NbO2 and Nb2O5 from DFT formalism. (April 2022) - Carvalho, R.C.; Mendonça, M.E.V.; Tavares, M.S.; Moreira, E.; Azevedo, D.L.
Abstract: All Niobium(Nb)-based materials have been widely investigated in recent decades due to a series of special applications in the high-tech industry, namely, in the aerospace sectors, for example, as metallic superalloys and, also, in the electro-electronic in which they are used as microcapacitors. We report the results of a theoretical study of the Niobium Dioxide (NbO2 ) and Niobium Pentoxide (Nb2 O5 ) which is based on the ab initio plane-wave pseudo-potential model from Density Functional Theory (DFT), within both the Local Density Approximation (LDA) and the Generalized Gradient Approximation (GGA), for the exchange and correlation potential. The structural properties, the electronic band structure, the electronic density of states, the reflectivity and the optical absorption are calculated from the nanostructures optimized at their lowest energy levels and, the comparison reveals good agreement of the calculated lattice parameters with theoretical and experimental results. An indirect bandgap E(ZΓ) was obtained within the GGA and LDA approximations of calculation for both NbO2 and Nb2 O5 . In addition, the optical absorptions and the reflectivities were shown to be sensitive to the plane of polarization of the incident light in the range of ultraviolet radiation to visible spectrum. The theoretical peaks of the infrared (IR) and Raman spectra in the frequency range of 0–1000 cm −1 was estimated and assigned, considering the norm-conserved pseudopotentials. The thermodynamic potentials, the specific heat at constant volume of the nanostructures are also calculated, which dependence on the temperature are specified. Highlights: We theoretically investigate the physical properties of NbO2 and Nb2 O5 nanostructures. The optical properties were presented showing some anisotropy in relation to the polarization of the incident radiation. The results show that the NbO2 become a little more stable energetically for applications that require thermal insulation.